2020
DOI: 10.3390/sym12060958
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Perturbation Iteration Method for Solving Fractional Model of Damped Burgers’ Equation

Abstract: The newly constructed optimal perturbation iteration procedure with Laplace transform is applied to obtain the new approximate semi-analytical solutions of the fractional type of damped Burgers’ equation. The classical damped Burgers’ equation is remodeled to fractional differential form via the Atangana–Baleanu fractional derivatives described with the help of the Mittag–Leffler function. To display the efficiency of the proposed optimal perturbation iteration technique, an extended example is deeply analyzed. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Deniz and Bildik presented the optimal perturbation iteration algorithms (OPIA) in 2016 [43]. It has been proven that these algorithms can be safely applied to many types of differential equations [44][45][46][47][48][49][50][51][52]. In this section, we give a short description of OPIA for systems of ordinary differential equation.…”
Section: Formulation Of Opias For Systems Of Ordinary Differential Eqmentioning
confidence: 99%
See 1 more Smart Citation
“…Deniz and Bildik presented the optimal perturbation iteration algorithms (OPIA) in 2016 [43]. It has been proven that these algorithms can be safely applied to many types of differential equations [44][45][46][47][48][49][50][51][52]. In this section, we give a short description of OPIA for systems of ordinary differential equation.…”
Section: Formulation Of Opias For Systems Of Ordinary Differential Eqmentioning
confidence: 99%
“…This technique has been applied to many types of ODEs and PDEs such as Bratu-type [43], Riccati differential equation [44], heat transfer equations [45], nonlinear systems [46], Lane-Emden types [47], generalized regularized long wave equations [48]. More studies can also be found in [49][50][51][52][53][54][55][56][57]. The rest of the current paper is planned as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Other important models including system of nonlinear coupled differential equations occurring in the phenomenon of fluid, 16,17 nonconservative dynamical system of a rotating electrical machine, 18 strongly nonlinear equation, 19‐21 delay differential equation, 22 nonlinear heat transfer equations, 23 Lane‐Emden‐type equations, 24,25 Fisher's equations, 26 Bratu‐type problems, 27 generalized regularized long wave equations, 28 Burgers's equation, 29 modified Boussinesq‐Burger equations, 30 coupled Drinfel'd‐Sokolov‐Wilson equation, 31 and Klein‐Gordon equations 32 . Other models that have been solved using this method can be found in References 33‐37 and references therein.…”
Section: Introductionmentioning
confidence: 99%